Implementasi Mobile Ad-Hoc Network Pada Daerah Pasca Bencana Dengan Protokol DSR - Alon Jala Tirta Segara; Aditya Wijayanto; Muhamad Azrino Gustalika; Afifah Dwi Ramadhani (STMIK Budi Darma, 2022)
Indonesia is one of the countries that has a very large potential for disaster. If a disaster occurs then all activities will stop because the infrastructure is damaged. One of the example is digital payment activitiy. It will stop because there are failure because the existing system is loss. The proposed research is to conduct modeling using cellular ad hoc networks (MANET). An Ad-Hoc network is a standalone configuration for configuring the network infrastructure of devices that can self-configure wirelessly connected devices. In its development, Mobile ad hoc networks can be used in many ways. One of the example is in disaster management. In this study, we recommend restructuring the network by using a mobile ad hoc network to replace network infrastructure damaged by disasters. We are trying to design a replacement network infrastructure to replace the damaged network infrastructure so that payment transactions can be carried out continuously until the restoration of the new network infrastructure can be built. The protocol used in this study is the DSR (Dynamic Source Routing) protocol, this protocol has the advantage of finding routes when there is damage to the links between nodes. From the simulation results using NS-2, by increasing the number of nodes in the simulation area, it shows that there is a decrease in packet loss to 0%. There is an increase in delivery success of almost 98% when the number of nodes is increased. And there is a decrease in delay with the addition of the number of nodes